Aging‐related histone modification changes in brain function - Ding, Yanwen; Liu, Chengxi; Zhang, Yi (Ibrain, 2023)
Aging can be defined as a decline of physiological function that is more difficult to reverse, characterized by the loss of the physiological integrity of tissues, organs, and cells of an organism over time. Normal aging is associated with structural and functional changes in the brain, involving neuronal apoptosis, synaptic structure, neurotransmission, and metabolism alterations, leading to impairment in sleep, cognitive functions, memory, learning, and motor and sensory systems. Histone modification is a significant aging‐related epigenetic change that influences synaptic and mitochondrial function and immune and stress responses in the brain. This review discusses the changes in histone modifications that occur during brain aging, specifically methylation and acetylation, and the associated changes in gene transcription and protein expression. We observed that genes related to synaptic and mitochondrial function are downregulated in the aging brain, while genes related to immune response and inflammatory functions are upregulated. Alterations in histone modifications play a key role in the loss of partial brain function due to aging. Decreased synaptic and mitochondrial function is a distinctive feature of aging, and these functionally related genes are often accompanied by a decrease in transcriptional activation modification and an increase in inhibitory histone modification during aging, which ultimately leads to a decrease in protein expression. Increased stress and immune responses are often observed during aging, resulting in increased protein expression due to opposite histone modifications in the genes associated with them. This review examines the changes in histone modifications, including methylation and acetylation, that take place as the brain ages and emphasizes the alterations in gene transcription and protein production that these modifications bring about throughout these functional decreases.